Characterization of Sb scaling and fluids in saline geothermal power plants: A case study for Germencik Region (Büyük Menderes Graben, Turkey). (November 2021) - Tonkul, Serhat; Baba, Alper; Demir, Mustafa M.; Regenspurg, Simona
Highlights: Scaling is one of the important problems in the geothermal system. Scaling reduces the efficiency of the plant and causes economical loss. Stibnite is one of the main scales formed in the Büyük Menderes Graben system. Seismic activity is also a phenomenon that supports the rise of fluids from deep to the surface. Stibnite can form in hydrothermal fluids due to changes in pH, temperature, and aqueous sulfide content. Abstract: Turkey is located on the seismically active Alpine-Himalayan belt. Although tectonic activity causes seismicity in the Anatolian plate, it also constitutes an important geothermal energy resource. Today, geothermal energy production is heavily concentrated in Turkey's Western Anatolia region. Graben systems in this region are very suitable for geothermal resources. The Büyük Menderes Graben (BMG) is an area of complex geology with active tectonics and high geothermal potential power. Germencik (Aydın) is located in the BMG, where the geothermal waters include mainly Na-Cl-HCO3 water types. This study examined the stibnite scaling formed in the preheater system of the Germencik Geothermal Field (GGF). The formation of the stibnite scaling on the preheater system dramatically reduces the energy harvesting of the GGF. Considering the stibnite scaling in the surface equipment, the optimum reinjection temperature was determined as 95 °C to prevent stibnite scaling in the GGF.